Znaczenie wczesnodziecięcego przywiązania w diadzie ‘matka/opiekun – dziecko - Włodarczyk, Ewa (Wydawnictwo Naukowe UAM, 2016)
The point of interest in this article is attachment, especially its properties, phase of development and types. It emphasizes the importance of early experiences of the child in interaction with a sensitive and reactive mother and the consequences of their absence and irregularities that may affect the child’s further mental, cognitive, emotional, and social development.
Significance of Early Childhood Attachment in the “Mother/Tutor – Child” Dyad
Keywords: attachment; motherhood; early childhood